2011
DOI: 10.1590/s1726-46342011000200013
|View full text |Cite
|
Sign up to set email alerts
|

El aumento de la expresión del ARNm de la enzima convertidora de angiotensina I homóloga (ECA-2) inducido por atorvastatina se asocia a menor fibrosis e hipertrofia ventricular izquierda en un modelo de cardiomiopatía diabética

Abstract: Our results indicate that atorvastatin, independently of its cholesterol-lowering capacity, lowers the ACE/ACE2 ratio to normal values and attenuates the development of adverse remodeling in the diabetic heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…A study by Tikoo et al found that atorvastatin can upregulate ACE2 expression in cardiac tissue when animals were fed high cholesterol diets [ 27 ]. Similar findings were reported by Aguilar et al in a murine model [ 28 ] and Li et al found rosuvastatin upregulated ACE2 expression in murine vascular smooth muscle cells [ 29 ]. Conclusions from these data highlight the beneficial role of statins in mediating attenuation of cardiovascular risk, however, amidst the current COVID-19 pandemic, there is concern about pharmacologic upregulation of the ACE2 receptor, for example with ACE-inhibitor treatment.…”
Section: Recommendationssupporting
confidence: 88%
“…A study by Tikoo et al found that atorvastatin can upregulate ACE2 expression in cardiac tissue when animals were fed high cholesterol diets [ 27 ]. Similar findings were reported by Aguilar et al in a murine model [ 28 ] and Li et al found rosuvastatin upregulated ACE2 expression in murine vascular smooth muscle cells [ 29 ]. Conclusions from these data highlight the beneficial role of statins in mediating attenuation of cardiovascular risk, however, amidst the current COVID-19 pandemic, there is concern about pharmacologic upregulation of the ACE2 receptor, for example with ACE-inhibitor treatment.…”
Section: Recommendationssupporting
confidence: 88%
“…In a diabetic rat model, the addition of fluvastatin (with insulin) improved cardiac ACE2 expression and decreased myocardial fibrosis when compared to rats treated with insulin alone [ 114 ]. Similar findings were reported in a rat model of diabetic cardiomyopathy, where the addition of atorvastatin improved ACE2 expression and normalized ACE/ACE2 ratio compared to control animals who did not receive atorvastatin [ 115 ]. Measurements of ACE2 mRNA expression were increased in rats who received rosuvastatin compared to controls after vascular balloon injury [ 116 ].…”
Section: Medicationssupporting
confidence: 84%
“…[23]. Pathological changes including cell apoptosis [24], fibrosis [25] and cardiac hypertrophy [26] are involved in DCM. More importantly, during the development of DCM, in addition to cardiac pump dysfunction due to loss of contractile units, malignant ventricular arrhythmias such as sudden cardiac death (SCD) were considered contributing more to the mortality in diabetic patients [27,28].…”
Section: Discussionmentioning
confidence: 99%